Materials for Potential EMI Shielding Applications Processing, Properties and Current Trends - Joseph, Kuruvilla; Joseph, Kuruvilla; Wilson, Runcy; Gejo, George (Elsevier Science, 2019)
Materials for Potential EMI Shielding Applications: Processing, Properties and Current Trends extensively and comprehensively reviews materials for EMI shielding applications, ranging from the principles to possible applications and various types of shielding materials. The book provides a thorough introduction to electromagnetic interference, its effect on both the environment and other electronic items, various materials that are used for electromagnetic interference shielding applications, and its properties. It explains the mechanism behind EMI shielding, the methods by which EMI SE of a given material is estimated, and the different fabrication methods currently employed for fabricating EMI shielding materials. Final sections focus on the theoretical background of EMI shielding and shielding mechanisms. This theoretical background is extended to the physics of EMI shielding, wherein the physics behind mechanism of shielding is explained. - Focuses on the different types of available EMI shielding, their applications, processing, characterization, and the mechanism behind their shielding - Discusses how to incorporate EMI shielding with low cost, low density and high strength - Provides an understanding and clarifies both elementary and practical problems relating to EMI shielding materials